Peran Motivasi Kerja Dalam Meningkatkan Kinerja Pegawai Sektor Publik - Filda Nurani Zebua; Dermawan Zebua (CV. SINAR HOWUHOWU, 2026)
Public sector employee performance is a key factor in determining the quality of public service and the effectiveness of government administration. One important determinant of employee performance is work motivation. This study aims to analyze the role of work motivation in improving public sector employee performance, both from an intrinsic and extrinsic perspective. The research method used was a quantitative approach using a survey technique of employees at a local government agency. Data were collected through a questionnaire developed based on indicators of work motivation and employee performance, then analyzed using descriptive and inferential statistics. The results indicate that work motivation has a positive and significant influence on public sector employee performance. Intrinsic motivation, such as responsibility, meaningful work, and opportunities for self- development, has been shown to provide a stronger contribution than extrinsic motivation. These findings emphasize the importance of leadership and organizational policies in creating a work environment that fosters sustainable employee motivation.